Use of deferoxamine (DFO) in transfusion-dependent β-thalassemia during pregnancy: A retrospective study - Maria Grazia Piccioni; Carmela Capone; Flaminia Vena; Valentina Del Negro; Michele Carlo Schiavi; Valentina D'Ambrosio; Antonella Giancotti; Maria Paola Smacchia; Roberto Brunelli (Elsevier, 2020)
Objective: To report cases of use of chelation therapy during pregnancy which resulted in favorable outcomes for the babies. Materials and methods: In this retrospective cohort study, we described the evolution and outcome of 9 pregnancies in Italian thalassemic women who received deferoxamine (DFO) inadvertently during early pregnancy. Results: The use of deferoxamine during first trimester did not lead to adverse effects on the fetus or cause major complications for the gestation, although an increase in iron burden was observed after suspending chelation therapy. Conclusion: In our experience, iron-chelation therapy might be administrated in pregnancy where the benefits to the mother outweigh the potential risks to the baby. Keywords: Deferoxamine, Iron chelation therapy, Magnetic resonance T2*, Pregnancy, Thalassemia